Monetary theory and policy from Hume and Smith to Wicksell : money, credit, and the economy - Arnon, Arie (Cambridge : Cambridge University Press, 2011)
This book provides a comprehensive survey of the major developments in monetary theory and policy from David Hume and Adam Smith to Walter Bagehot and Knut Wicksell. In particular, it seeks to explain why it took so long for a theory of central banking to penetrate mainstream thought. The book investigates how major monetary theorists understood the roles of the invisible and visible hands in money, credit and banking; what they thought about rules and discretion and the role played by commodity-money in their conceptualizations; whether or not they distinguished between the two different roles carried out via the financial system - making payments efficiently within the exchange process and facilitating intermediation in the capital market; how they perceived the influence of the monetary system on macroeconomic aggregates such as the price level, output and accumulation of wealth; and finally, what they thought about monetary policy.
Part I. Analytical and Historical Foundations: 1. Monetary theory circa 1750: David Hume; 2. Mid eighteeth-century British financial system; 3. Adam Smith: the case for laissez-faire in money and banking; 4. 'Monetary theories of credit' in exchange -- Part II. Debating Monetary Theory under Inconvertibility: 5. New reality: the restriction period 1797-1821; 6. The early round of the Buillion Debate, 1800-1802: Boyd versus Baring; 7. Thornton on inconvertibility and central banking: ahead of his times; 8. Ricardo versus Bosanquet: the famous round in the Bullion debate; 9. 'Credit theories of money' in exchange and intermediation -- Part III. Debating: Laissez-Faire, Rules and Discretion: 10. From the resumption to 1837: more crises; 11. The currency school trio: Loyd, Torrens, and Norman; 12. The banking school trio: Tooke, Fullarton, and Wilson; 13. Neither currency nor banking school: Joplin and the "free banking" Parnell -- Part IV. The Road to Defensive Central Banking: 14. Bagehot and a new conventional wisdom; 15. Does Karl Marx fit in?; 16. Marshall's (oral) monetary tradition and bimetallism -- Part V.A New Beginning: Towards Active Central Banking: 17. Wicksell's innovative monetary theory and policy; 18. The puzzling slow rise of a theory of central banking: between the lender of last resort, defensive, and active monetary policy.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Monetary policy -- History; Banks and banking, Central -- History; Economists